The observation of resistive switching characteristics using transparent and biocompatible Cu2+-doped salmon DNA composite thin film. (23rd May 2019) - Abbas, Yawar; Dugasani, Sreekantha Reddy; Raza, Muhammad Tayyab; Jeon, Yu-Rim; Park, Sung Ha; Choi, Changhwan
Abstract: For the potential switching bio-memory device application using DNA composite thin film, we fabricated and characterized the transparent and biocompatible resistive switching random access memory (RRAM) device within the structure stacking of Pt/Cu 2+ doped salmon DNA/FTO, where Cu 2+ doping into salmon DNA was solution-processed. The device shows good bipolar switching characteristics with SET and RESET processes at negative and positive sweeps, respectively, with switching memory window greater than 10 3 ratios. The device was observed to be in low resistance state as its pristine state and an initial RESET state was necessary to achieve programmable SET and RESET cycles. Based on the electrical characteristics of the Cu 2+ -doped salmon DNA-based RRAM device we propose a switching mechanism with the formation and rupture of conductive filaments due to the migration of Cu 2+ during the electrical stress. Our understanding could contribute to the engineering of biomaterial memory switching medium for the environmentally benign, biocompatible and biodegradable memory storage devices.